Hyalohyphomycosis (Fusariosis): Atypical presentation in an immunocompetent individual responding to itraconazole - Deepthi Konda; Pradeep Balasubramanian; Saritha Mohanan; Laxmisha Chandrashekhar (Wolters Kluwer Medknow Publications, 2024)
Hyalohyphomycosis includes infections caused by various fungal species that produce hyaline, septate, branched hyphae. Fusarium is one such species which usually causes multiple papulo-nodules, ecthyma gangrenosum-like ulcers in immunocompromised individuals. Also, fusariosis is usually difficult to manage and responds favorably to amphotericin B, voriconazole, and posaconazole in disseminated cases. Here, we report an atypical case of cutaneous fusariosis in an immunocompetent individual who presented with multiple large cystic swellings, psoriasiform plaques, and palmoplantar keratoderma, and the patient responded completely to itraconazole.